2022
DOI: 10.3390/app12020856
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Segment-Level Crash Risk Prediction Using Advanced Data Modeling with Proactive and Reactive Crash Data

Abstract: Highway crashes, along with the property damage, personal injuries, and fatalities that they cause, continue to present one of the most significant and critical transportation problems. At the same time, provision of safe travel is one of the main goals of any transportation system. For this reason, both in transportation research and practice much attention has been given to the analysis and modeling of traffic crashes, including the development of models that can be applied to predict crash occurrence and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Using the CART model, results showed that influential factors were mostly similar between daylight crashes and crashes that happened on lighted streets at night. However, dark streets at night were able to involve some other factors in the severity of twovehicle crashes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Using the CART model, results showed that influential factors were mostly similar between daylight crashes and crashes that happened on lighted streets at night. However, dark streets at night were able to involve some other factors in the severity of twovehicle crashes [19].…”
Section: Discussionmentioning
confidence: 99%
“…As it remained only 15 fatal crashes after eliminating unknown records, fatal and injury crashes were integrated. Therefore, the dependent variable is a binary variable with the value of 1 if the crash severity is fatal or injury; and 0 if the crash severity is no injury [3]. The dataset includes 1403 injury/fatal and 4786 no injury vehicle-to-vehicle crashes.…”
Section: Figure 1 Study Areamentioning
confidence: 99%
“…The five categories of contributing factors to traffic collisions are human, vehicle, road, environment, and traffic [2,3]. Research has shown that human factors play a significant role in about 90% of crashes [4].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that according to the World Health Organization (WHO), 1.2 million individuals are amongst the annual casualties of traffic accidents, and approximately 20-50 million are found injured each year globally. Furthermore, approximately 17,000 individuals lose their lives in Iran annually due to traffic accidents; plus, the obtained results from the city of Rasht during a period of four years showed a total of 122 fatal and approximately 9,000 injured crash records [2,3]. Contrary to the accidents, which are usually presumed to be random events, the spatial distribution of traffic accidents in the road network is not random, and areas with high traffic accident frequency are essentially called blackspots or hotspots.…”
Section: Introductionmentioning
confidence: 99%